KESULITAN MAHASISWA PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU PADA JLPT (JAPANESE LANGUAGE PROFIENCY TEST) - Dzulfaqar Dzulfaqar; Hadriana Hadriana; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Difficulty in learning evaluation is a problem felt by students when taking a test or exam that is followed, both internally. This study discusses the difficuslties faced by the 2017& 2018 student of the Japanese Language Education Study Program Fkip Riau University at JLPT. The purpose of this study was to find out what difficulties were faced by students when participsting in the JLPT in 2019. The method used in this study was qualitative research. The results of this study indicate that 2017 & 2018 student have difficulty in internal factors, namely the dokkai and kanji sections. This is due to a lack of mastery of vocabulary, bunpou, and kanji material. In addition, external factors have no influence at all on the difficulties faced by students of the 2017 & 2018 batch of the Japanese Language Education Study Program, FKIP, Riau University at JLPT.Key Words: Error analysis, accent, intonation